Perbedaan Aktivasi Otot Ekstensor Lumbal pada 3 Posisi Statis - Romadhon, Aditya Johan; Nugroho, Fendy; Haryatno, Pajar (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Postural control plays a major role in maintaining postural adjustment during daily activities. Calculating body position should be precisely accurate toward gravitational forces to maintain neutral body alignment. Neutral body alignment is influenced by postural muscle activation and kinematics. In static positions, such as standing and sitting, there are different lumbo-pelvic kinematics. Objectives: The purpose of this study was to compare lumbar extensor activation during three static positions: standing, sitting on a chair, and sitting on the floor. Methods: this study uses cross sectional observational method 15 healthy subject was randomly recruited during this observational study, performing three static positions, standing, sitting on a chair and sitting on the floor while Surface Electromyograph (sEMG) placed on erector spine in lumbar segment, we recorded muscle activation on EMG monitor in those three static positions and compared to each static positions. Results: sEMG activation erector spine data in this study showed erector spine muscle activation increased during standing was 12.95 ± 0.94 µV, sitting on a chair was 2.63 ± 0.82 µV and sitting on the floor with mean erector spine activation was 2.63 ± 0.82 µV, in one way ANOVA between and within Group was p < 0.001. Conclusion: erector spine muscle activation during standing are greater than sitting on a chair with mean differences value was 5.6 µV and erector spine muscle activation during sitting on a chair are greater than sitting on the floor with flexed knee with mean differences was 4.62 µV. Keywords: Erector spine activation, Static position, Surface electromyograph, Neutral body alignment